সামটা : আর্সেনিক দূষণে আক্রান্ত একটি গ্রাম - পারভীন, মনজুয়ারা, ১৯৭১-
On ground water contamination with Arsenic and related health issues, chiefly with reference to Sāmaṭā, a village in Jessore District, Bangladesh.